Integrated Chalcogenide Photonics for Microresonator Soliton Combs (Laser Photonics Rev. 17(3)/2023). Issue 3 (13th March 2023) - Xia, Di; Yang, Zelin; Zeng, Pingyang; Zhang, Bin; Wu, Jiayue; Wang, Zifu; Zhao, Jiaxin; Huang, Jianteng; Luo, Liyang; Liu, Dong; Yang, Shuixian; Guo, Hairun; et al.
Abstract : Bright Soliton Microcombs In article number 2200219, Bin Zhang, Zhaohui Li, and co‐workers have generated a soliton microcomb based on a home‐developed integrated chalcogenide glass‐GeSbS chip, with the overall pumping power of the ten‐milliwatt level. In particular, both a bright soliton‐based microcomb with a bandwidth of 280 nm (≈1440–1680 nm) and a dark‐pulse comb with a bandwidth of 80 nm (≈1510–1590 nm) are generated pumped in a single GeSbS microresonator.